Practical Guide for the Prescription of Malaria Chemoprophylaxis for the Primary Care Physician - Meléndez-González, Héctor J.; González-Claudio, Glenda M. (Puerto Rico Health Sciences Journal, 2020)
Malaria is considered an important health threat around the world. Travelers from non-endemic countries are at risk of contracting the parasite that causes malaria. Those traveling on humanitarian missions and military personnel are at the greatest risk. Mosquito avoidance is an important intervention, but chemoprophylaxis is the most effective method for the prevention of this infection. The selection of a specific regimen can be a difficult task. It is a decision that is not based solely on the region in which a given patient is traveling but also on that patient’s comorbidities and the potential adverse effects of the medications to be used. This review is intended to be a simple guide for the primary care physician. We discuss the selection of chemoprophylaxis for patients in the general population. We also address the specifics of chemoprophylaxis during pregnancy and breast feeding and in people diagnosed with epilepsy.